Ownership Dynamics and Firms’ Performance: Influence of Large and Managerial Ownership on Pakistan’s Non- Financial PSX Firms (Journal of Asian Development Studies, 2025)
The aim of the study is to empirically identify the impact of shareholder pattern on firm performance in Pakistan. In this study the shareholder pattern is taken as independent variable and firm performance is taken as a dependent variable by considering the non-financial firms listed in Pakistan Stock Exchange for the period of 2015-2024. Simple random sampling technique is used by selecting the 73 firms. Secondary data were collected from the annual reports and regression analysis is used to analyze the data to test the hypotheses the statistical software SPSS 22. The results of this study show that shareholder pattern have significant relationship with performance considering the return on assets and Tobin’s Q. It is concluded that the managerial ownership and large ownership is perceived to be one of the key determinants of firm performance in non-financial firms. The managers should work in the direction where owner-manager can catch the target of aligning their interests being major stakeholders of the firm. The Findings of another dependent variable that is Tobin’s Q represents that whole model shows significant association among contribution of shareholder and firm performance (Tobin’s Q). Study recommends that larger ownership is an important aspect of Pakistani firms because these shareholders efficiently monitor the resources to increase the firm performance so firms should have to motivate the large shareholders to increase the performance of non-financial firms.